2021
DOI: 10.3390/ph14090933
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychiatric Disorders and COVID-19: What We Know So Far

Abstract: SARS-CoV-2 (Severe Acute Respiratory Syndrome Coronavirus-2) affects the central nervous system (CNS), which is shown in a significant number of patients with neurological events. In this study, an updated literature review was carried out regarding neurological disorders in COVID-19. Neurological symptoms are more common in patients with severe infection according to their respiratory status and divided into three categories: (1) CNS manifestations; (2) cranial and peripheral nervous system manifestations; an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 149 publications
(203 reference statements)
0
12
0
Order By: Relevance
“…Fifteen percent of patients presented neuro-psychiatric symptoms requiring treatment. These disorders are well-described in the literature and could be linked to a direct action of the virus on the nervous system [38,39].…”
Section: Discussionmentioning
confidence: 94%
“…Fifteen percent of patients presented neuro-psychiatric symptoms requiring treatment. These disorders are well-described in the literature and could be linked to a direct action of the virus on the nervous system [38,39].…”
Section: Discussionmentioning
confidence: 94%
“…However, direct neuroinvasion as a cause of seizure is currently controversial, with a number of studies failing to find viral RNA in CSF. Elevated levels of inflammatory cytokines, including IL-6, IL-1β, and TNF-α, have been found in patients following acute febrile seizures and a dysregulated cytokine surge in response to COVID-19 infection has been proposed as a possible etiology of seizure [1].…”
Section: Seizurementioning
confidence: 99%
“…While many COVID-19 patients may exhibit mild neurologic symptoms, a small percentage of patients can develop severe neurologic disorders [1]. Soon after the discovery of the illness, and the World Health Organization declaring COVID-19 a global pandemic, clinicians began reporting delirium and encephalitis in acutely ill patients with confirmed infection [2], and early retrospective studies coming out of China [3] and France [4] indicated that significant proportions of patients were experiencing neurologic complications during COVID-19 hospitalization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the fundamental mechanism of neuropsychiatric disorders in COVID-19 might be due to cytokine-induced disruption of the BBB, neuroinflammation, and peripheral neuronal injury, or due to direct SARS-CoV-2 neurotropism (Majolo et al 2021 ). Noteworthily , exaggerated inflammatory responses could be the suggested mechanism for the progression of neuropsychiatric and other neurological disorders in COVID-19 (Kumar et al 2021 ).…”
Section: Covid-19 and Neurological Manifestationsmentioning
confidence: 99%